2022
DOI: 10.24251/hicss.2022.292
|View full text |Cite
|
Sign up to set email alerts
|

Public Service Values and Chatbots in the Public Sector: Reconciling Designer efforts and User Expectations

Abstract: Chatbots are deployed across a wide range of public services, frequently to manage the increased volumes of online service requests. The appropriateness of many chatbot initiatives is often challenged. One reason for this is these initiatives are largely driven by agency centric goals, often neglecting the expectations of other public stakeholders. A public service value perspectivefounded on the notion of public valueoffers an avenue to represent the views of other public stakeholder groups. We examine the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Key among the factors were performance expectancy and effort expectancy. This finding is fully in line with existing theory of technology acceptance (e.g., Davis, 1989, Venkatesh et al, 2012, and also in line with the findings of a recent vignette study of government chatbot usage scenarios (Makasi et al, 2022).…”
Section: Citizen Perceptions Of Government Chatbots and Implications ...supporting
confidence: 92%
See 1 more Smart Citation
“…Key among the factors were performance expectancy and effort expectancy. This finding is fully in line with existing theory of technology acceptance (e.g., Davis, 1989, Venkatesh et al, 2012, and also in line with the findings of a recent vignette study of government chatbot usage scenarios (Makasi et al, 2022).…”
Section: Citizen Perceptions Of Government Chatbots and Implications ...supporting
confidence: 92%
“…At the same time, van Noordt and Misuraca (2019) note that current government chatbots typically provides generic information to citizens reflecting service triage rather than service negotiation. Prospective users of government chatbots have been found to value accuracy, availability, efficiency, and effectiveness (Makasi et al, 2022).…”
Section: Chatbots As Part Of Digital Governmentmentioning
confidence: 99%
“…There is a growing body of knowledge on how users experience government chatbots. Makasi et al [26], in an interview study with users and designers of government chatbots, found that such chatbots were perceived to enable increased effectiveness and efficiency in service provision, while potentially also strengthening accessibility and ease-of-use for government services. Abbas et al [1], in an interview study with municipality chatbot users, found users to appreciate the navigation support provided by the chatbot and its potential for simplifying access to government information.…”
Section: Government Chatbotsmentioning
confidence: 99%
“…They realise that adopting a responsible approach in the innovation process is not only beneficial for society but also crucial for maintaining a positive brand image and securing long-term success in an ever-changing market [25][26][27]. As stakeholders demand greater accountability and consumers seek out ethically sound products and services, the RIT concept has become a key driver in guiding corporates' future technological development direction [10,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%